Effects of interband transitions on Faraday rotation in metallic nanoparticles - Wysin, Gary M.; Chikan, Viktor; Young, Nathan; Dani, Raj Kumar (My University, 2013)
The Faraday rotation in metallic nanoparticles is considered based on a quantum model for the dielectric function epsilon(ω) in the presence of a DC magnetic field B. We focus on effects in epsilon(ω) due to interband transitions (IBTs), which are important in the blue and ultraviolet for noble metals used in plasmonics. The dielectric function is found using the perturbation of the electron density matrix due to the optical field of the incident electromagnetic radiation. The calculation is applied to transitions between two bands (d and p, for example) separated by a gap, as one finds in gold at the L-point of the Fermi surface. The result of the DC magnetic field is a shift in the effective optical frequency causing IBTs by ±μ[subscript B]B/ħ, where opposite signs are associated with left/right circular polarizations. The Faraday rotation for a dilute solution of 17 nm diameter gold nanoparticles is measured and compared with both the IBT theory and a simpler Drude model for the bound electron response. Effects of the plasmon resonance mode on Faraday rotation in nanoparticles are also discussed.
Keywords: Quantum Faraday rotation; Dielectric function; Interband transitions; Nanoparticles; Plasmons